Comparing the Effectiveness of Sexual Cognitive-Behavioral Education and Sexual Well-Being Education on Sexual Satisfaction and Sexual Self-Efficacy of Couples with Low Sexual Well-Being - Salak, Narges; Atashpour, Seyed Hamid (KMAN Counseling & Psychology Nexus, 2025)
The present study aimed to compare the effectiveness of sexual cognitive-behavioral education and sexual well-being education on sexual satisfaction and sexual self-efficacy of couples with low sexual well-being. This study employed a quasi-experimental design with a pre-test, post-test, and follow-up, including experimental and control groups. The statistical sample consisted of 90 participants, comprising 45 couples, selected using a systematic random sampling method and assigned to three groups. The research instruments included the Sexual Well-Being Questionnaire, the Sexual Satisfaction Questionnaire, and the Sexual Self-Efficacy Questionnaire. Repeated measures analysis of variance (ANOVA) was used for statistical analysis. The results indicated that the implemented interventions were effective in improving sexual satisfaction and sexual self-efficacy in couples with low sexual well-being, with significant differences observed between the groups in the post-test and follow-up stages (p < .05, p < .01). The findings of this study indicate that both cognitive-behavioral sexual education and sexual well-being education effectively enhance sexual satisfaction and sexual self-efficacy among couples with low sexual well-being. However, sexual well-being education demonstrated greater effectiveness in improving sexual attitude and quality of sexual life.